Design and Synthesis of Xanthone Analogues Conjugated with Aza‐aromatic Substituents as Promising G‐Quadruplex Stabilizing Ligands and their Selective Cancer Cell Cytotoxic Action. (17th January 2023) - Roy, Soma; Chakraborty, Nirmal; Maiti, Bappa; Muniyappa, Kalappa; Bhattacharya, Santanu
Abstract: We have examined the stabilization of higher‐order noncanonical G‐quadruplex (G4) DNA structures formed by the G‐rich sequences in the promoter region of oncogenes such as c‐MYC, c‐KIT, VEGF and BCl2 by newly synthesized, novel nitrogen‐containing aromatics conjugated to xanthone moiety. Compounds with N‐heterocyclic substituents such as pyridine (XNiso), benzimidazole (XBIm), quinoxaline (XQX) and fluorophore dansyl (XDan) showed greater effectiveness in stabilizing the G4 DNA as well as selective cytotoxicity for cancer cells (mainly A549) over normal cells both in terms of UV‐Vis spectral titrations and cytotoxicity assay. Both fluorescence spectral titrimetric measurements and circular dichroism (CD) melting experiments further substantiated the G4 stabilization phenomenon by these small‐molecular ligands. In addition, these compounds could induce the formation of parallel G4 structures in the absence of any added salt condition in Tris⋅ HCl buffer at 25 °C. In a polymerase stop assay, the formation of stable G4 structures in the promoter of oncogenes and halting of DNA synthesis in the presence of the above‐mentioned compounds was demonstrated by using oncogene promoter as the DNA synthesis template. Apoptosis‐mediated cell death of the cancer cells was proved by Annexin V‐PI dual staining assay and cell‐cycle arrest occurred in the S phase of the cell cycles. The plausible mode of binding involves the stacking of the xanthone core on the G4 DNA plane with the possibility of interaction with the 5'‐overhang as indicated by molecular dynamics simulation studies. Abstract : Not for normal cells : Xanthone aza‐aromatic derivatives stabilize higher‐order noncanonical G‐quadruplex (G4) DNA structures. Various biophysical experiments substantiated G4 stabilization by these promising small‐molecular ligands. Compound‐induced selective cytotoxic action in cancer cells over normal cells exhibited the potency of these small‐molecules for use in anticancer therapeutics.